Pelatihan Pengembangan Soal Ranah Kognitif Untuk Guru Madrasah Ibtida’iyah Lombok - Awiria Awiria; Asrori Yudha Prawira; Dariyanto Dariyanto; Intan Aprilia; Intan Sari Pujayanah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Community service carried out aims to improve the ability to make questions, especially the cognitive domain. Efforts were made in the form of an explanation of the cognitive domain, then continued with the practice of making the cognitive domain. This activity was carried out online at Madrasah Ibtida'iyah Darus Shiddiqien NW Mertakpaok Lombok. Madrasah Ibtida'iyah Darus Shiddiqien NW Mertakpaok Lombok needs a refresher in making questions that are in accordance with the rules of writing questions, especially the cognitive domain. The evaluation of learning that will be trained is making questions in the cognitive domain which still require accuracy in choosing the right operational words. This activity can provide new insights on how to make questions that are in accordance with the rules and theories at Madrasah Ibtida'iyah Darus Shiddiqien NW Mertakpaok Lombok